An electrodeposition strategy for the controllable and cost-effective fabrication of Sb-Fe-P anodes for Li ion batteries. (20th June 2019) - Zheng, Xiao-Mei; Rong, Wen-Qian; You, Jin-Hai; Tu, Guo-Ping; Zhang, Peng-Yue; Tao, Shan; Wang, Yun-Xiao; Huang, Ling; Li, Jun-Tao
Abstract: Ternary thin-film Sb-Fe-P anodes prepared by scalable and cost-effective electroplating are examined as prospective anodes for lithium-ion batteries (LIBs). The optimum Sb48 Fe36 P16 anode has high reversible charge capacity of 588 mAh g −1  at 100 mA g −1 with an initial coulombic efficiency of 77.5% and 87.5% capacity retention after 50 cycles. Further, this anode shows good rate capability (460 mAh g −1  at 1 A g −1 ). The discharge/charge mechanism of Sb48 Fe36 P16 versus Li was revealed by ex situ X-ray diffraction (XRD) and in situ electrochemical impedance spectroscopy (EIS). The good electrochemical performance of the optimal Sb48 Fe36 P16 anode is attributed to the active/inactive metal matrix and its unique microstructure. The good electrochemical properties of the ternary binder-free Sb48 Fe36 P16 thin film make them promising candidates for anodes in LIBs. Because of its cost-effectiveness and suitability for large-scale manufacture, this facile electrodeposition strategy can be applied to prepare thin-film anodes for energy storage systems.